European Investment Bank Activity Report 2021 The innovation response - European Investment Bank (European Investment Bank, 2022)
Our flagship report illustrates how the European Investment Bank Group confronted two great threats in 2021, the climate crisis and the coronavirus pandemic, even as the challenges posed by development grew more urgent. The EU bank tackled these hazards by thinking hard and moving fast - in new directions. The Activity Report highlights our emergency response to COVID-19 through the unique European Guarantee Fund, as well as our support for healthcare companies working on cures and therapies for the disease. It illustrates the dimensions of our backing for companies that are forging new frontiers of climate action - sometimes right into outer space. It demonstrates our commitment to a better future for all Europeans in our cohesion investment and for all global citizens through our development work. Built around 25 articles about the work of the European Investment Bank and the European Investment Fund in COVID-19 response, climate action, cohesion and development, the Activity Report highlights our contribution to a healthy, green and inclusive world. Figures are expected outcomes of financed new operations signed in 2021 for the first time based on available data at this stage. All figures are unaudited and provisional.